(untitled) (Research, Society and Development, 2021)
Medicinal mistletoes are also used in cancer therapies. Mitotic effects of the aqueous leaf extract of Phoradendron piperoides (Kunth) Trel. were evaluated. The plant material was collected in Cáceres, Mato Grosso, Brazil, in 2017. The test with three concentrations of aqueous leaf extract (0, 6 and 18 g of leaf powder/500 mL of water) was applied to Allium cepa L. Newly-emitted onion roots were immersed in the solution for 24 hours (action) and another 24 hours in water (recovery). Roots were collected for microscopy and cell counting was used to calculate the mitotic indices (MI%), which showed a lower value at the highest concentration than the intermediate concentration (3.95% c < 16.80% b), both differing from the control (60.40% a). Mitosis inhibition increased with an increase in extract concentration. The mitotic indices in the control of action and recovery tests were similar (60.47%) but higher than in the other concentrations. The indices were higher (3.95% B < 46.00% A) at intermediate doses (16.80% B < 36.60% A) and lower (p < 0.05) in the action than the recovery considering the overall average (27.05% B < 47.71% A). Thus, P. piperoides has bioactive compounds extracted in water that are inhibitors of mitosis, dose-dependent, and partially reversible effects on recovery.